High-stakes testing policy and English language teaching: Voices of the leftovers - Laser Romios; Ashadi Ashadi; Widyastuti Purbani (Journal on English as a Foreign Language, 2020)
High-stakes testing has been controversial in many countries for several impacts and reasons surrounding its implementation. Teachers’ voices should be heard for well-rounded education policy. This study aims to investigate the voices of English teachers on the impacts of the national exam (NE) towards English language teaching at junior high schools (JHS) in Yogyakarta, Indonesia. It is a qualitative study involving three private JHSs and three state JHSs, chosen according to their NE-based ranks: low, mediocre, and high performing – for inclusive representation. The subjects are six English teachers from six JHSs. The data were collected through interviews and analyzed using the analysis model of Miles, Huberman, and Saldana, following the steps of data condensation, data categorization, data display, data interpretation, and conclusion drawing and verification. The findings show that NE leads to low order thinking skills, digresses from the goals of curriculum 2013, prioritizes only knowledge, focuses on English passive skills, induces favoritism between teachers, and disables teachers to vary their teaching strategies. Teachers’ involvement in education policy is necessary, and they are generally in favor of the NE abolishment plan. The implication of this study calls for implementing teachers' coping mechanism in transitioning from NE to the newly proposed assessment.